Microsoft Publisher 2000 complete concepts and techniques - Shelly, Gary B. (Shelly Cashman series, 2000)
Part of the highly successful Shelly Cashman series, this texts offers a clear, step-by-step, screen-by-screen approach to learning Microsoft Publisher 2000 skills.